Pendekatan Polinomial Ortogonal dalam Menentukan Dosis Optimum NPK Grower pada Tanaman Sawi - Rita Rida Simamora; Olivia Cindowarni; Nyuzza Fajar Annaba; Usman Rizal; Firza Afrina (AgriMalS, 2026)
Analysis of variance (ANOVA) is a basic statistical method used to determine whether or not treatments have an effect on the observed response variables. Orthogonal polynomial analysis is a follow up test that functions to break down response trends into linear, quadratic, or higher order components. This study aimed to determine the analysis of variance and orthogonal polynomial analysis on the growth response of mustard greens (Brassica juncea) under various doses of NPK Grower fertilizer. The study was conducted using a Randomized Block Design (RBD) with 5 treatment levels G0 = Control (without NPK Grower), consist of G1 = 1 g/polybag, G2 = 2 g/polybag, G3 = 3 g/polybag, G4 = 4 g/polybag. The results of the follow up analysis using orthogonal polynomials showed that most plant growth responses followed a quadratic pattern, particularly in the variables of plant height, number of leaves, stem diameter, and fresh plant weight. This indicates the presence of an optimum dose capable of producing maximum growth. The optimum dose of NPK Grower fertilizer ranged from approximately 3.14 to 3.42 g/polybag, with an average value of around 3.2–3.3 g/polybag producing maximum growth results. In the root length variable, the response pattern was linear, meaning that increasing fertilizer doses continued to enhance root growth without reaching an optimum point within the tested dose range. The combination of analysis of variance and orthogonal polynomial analysis was able to provide more comprehensive information regarding the effect of NPK Grower.